Compatibilidade anatômica dos porta-enxertos Pyrus calleryana e Chaenomeles sinensis com pereiras, macieiras e marmeleiros - Melo, Evaldo Tadeu de (2016)
Grafting has been widely used in the production of seedlings, however, it is important to point out the difficulty in affinity between scion-rootstocks. Even with the significant progress made in recent decades and development of new cultivars, there is lack of rootstocks adapted to mild winter conditions. In this sense, the aim of this study was to evaluate the anatomical compatibility of pomaceas cultivars on rootstocks Pyrus calleryana e Chaenomeles sinensis, analyzing the connection of vascular tissues from secondary xylem, to detect compatible combinations, aiming the expansion of pears cultivation, quince and apple trees in subtropical regions. Three experiments were conducted, the first consisting of eleven pear cultivars, the second of two cultivars of quince and the third for three apple cultivars, all grafted on rootstocks of Pyrus calleryana and Chaenomeles sinensis. In each experiment was used a completely randomized design, with five replications and 10 grafts per plot. Was evaluated the percentage of sprouting per graft at 60 days, the length and diameter of the shoots and anatomical analyzes 120 days after grafting, cuts being made in cross and longitudinal sections. There were no significant differences between the anatomical elements of the secondary xylem of all species used in trials. The pear trees showed good rate of budding, but the development occurred only on the Pyrus calleryana and in anatomical assessment it was observed that the vascular tissues were connected, which did not occur on the Chaenomeles sinensis. The quince tree also showed good rate of budding and developed well on both rootstocks with good connection of vascular tissues. The apple trees had small development on the Pyrus calleryana rootstock, with connecting of a few vascular tissues, on the Chaenomeles sinensis there was no development of the graft and connection of vascular tissues. It is concluded that the budding graft does not indicate success in grafting intergeneric; the connection of tissues is fundamental to the success of grafting and the greater the connection of vascular tissues the greater the development of the future plant; pear trees have no compatibility with the Chaenomeles sinensis; the quinces have compatibility with both rootstocks; the apple trees have incompatibility with Chaenomeles sinensis, and only the cultivar Princess developed on Pyrus calleryana.